Red-bed mudstone premixed flow state solidified soil and curing agent and preparation method of red-bed mudstone premixed flow state solidified soil

By using a curing agent combined with organic and inorganic in the pre-mixed fluid solidified soil of red mudstone, the problems of poor fluidity, low early strength and easy softening, disintegration, expansion and expansion of the red mudstone pre-mixed fluid solidified soil are solved, and the effects of high fluidity, high early strength and low dry shrinkage strain are achieved, and the engineering application performance is improved.

CN119899009APending Publication Date: 2025-04-29SICHUAN INSITITUTE OF BUILDING RES +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510018865.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-07
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

The premixed fluid solidified soil of red mudstone is poor in the construction process, has low early strength, and contains expansive clay minerals, which leads to softening, disintegration, expansion and expansion, affecting the performance of the engineering application.

Method used

The curing agent is prepared by combining organic and inorganic methods, including ordinary silicate cement, sulfoaluminate cement, alkali residue powder, composite mineral blends, surfactants and polymers, and the red mudstone premixed fluid solidified soil is prepared evenly by premixing and stirring.

Benefits of technology

The fluidity and early strength of the premixed fluid solidified soil of red mudstone are improved, the dry shrinkage strain is reduced, the engineering application performance is improved, and the problem of insufficient backfill soil density during construction is solved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of building materials, and particularly discloses red-layer mudstone premixed flow-state solidified soil, a curing agent and a preparation method thereof.The curing agent is prepared from, by mass, 30 parts of ordinary Portland cement, 3-15 parts of sulphoaluminate cement, 3-15 parts of alkaline residue powder, 18-90 parts of composite mineral admixture and 5-8 parts of surfactant. 2-5 parts of a high-molecular polymer; the composite mineral admixture comprises the following components in parts by mass: 20 parts of lithium slag powder, 3-20 parts of magnesium slag powder and 5-15 parts of blast furnace ferronickel slag powder. The method has the advantages that the shrinkage strain is reduced on the premise that the fluidity and the early strength of the red-layer mudstone premixed flow-state solidified soil meet the construction requirements of the premixed flow-state solidified soil, and the engineering application performance of the red-layer mudstone is greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building materials, in particular to a production technology of premixed fluidized solidified soil of red bed mudstone. Background Art

[0002] At present, the construction method of solidified soil mainly adopts in-situ mixing and mechanical compaction, but in-situ mixing and mechanical compaction are easily restricted by the construction site. When faced with the situation of narrow foundation pit backfill space, complex underground integrated pipeline corridor, and multiple narrow and independent backfill sections on the construction surface, in-situ mixing is subject to construction restrictions, and compaction machinery cannot be used. The use of manual compaction is likely to cause the problem of insufficient density of backfill soil. Fluidized solidified soil is a new type of environmentally friendly backfill material. It is a high-flowability and high-density building material formed by mixing soil, curing agent and water according to a certain ratio.

[0003] Red mudstone is a widely distributed special soil with unfavorable engineering characteristics such as high porosity, high liquid limit, high plasticity, low compaction, and easy shrinkage due to water loss. The special engineering characteristics easily lead to engineering problems such as roadbed collapse, ground cracking, and slope instability during construction. Therefore, it is necessary to improve the red mudstone or reduce the standard for use, and the demand for premixed fluidized solidified soil has been greatly increased.

[0004] However, the construction and application of premixed fluidized solidified soil for red mudstone currently have the following problems: (1) The premixed fluidized solidified soil of red mudstone has poor fluidity and needs to be spread and vibrated manually during the construction process.

[0005] (2) In order to achieve higher fluidity, the slurry concentration can only be reduced, resulting in a long setting time for the solidified soil, low early strength, and a long construction period. It often takes at least 24 hours before the next construction operation can be carried out.

[0006] (3) Red mudstone contains a large amount of expansive clay minerals such as montmorillonite, which are easy to soften, disintegrate, expand and swell when exposed to water, and have a fast weathering rate. When used as premixed fluidized solidified soil, it seriously affects the early strength and fluidity and is more prone to shrinkage and cracking in the later stage. The traditional improvement method is prone to shrinkage and cracking when improving the premixed fluidized solidified soil of red mudstone.

[0007] Therefore, based on the above problems, the present invention focuses on the difficulty that red mudstone is easy to soften, disintegrate, and expand, and adopts a combination of organic and inorganic methods to prepare a curing agent, give full play to the synergistic effect of various materials, and prepare red mudstone premixed fluidized solidified soil with low shrinkage strain and high early strength. Summary of the invention

[0008] In order to reduce the shrinkage strain of red mudstone premixed fluidized solidified soil while ensuring that its fluidity and early strength meet the construction requirements of premixed fluidized solidified soil, the present invention provides a red mudstone premixed fluidized solidified soil and a curing agent and a preparation method thereof.

[0009] The technical scheme adopted by the present invention is: a method for preparing a special curing agent for premixed fluidized solidified soil of red mudstone, wherein the production raw material formula comprises the following components in the following mass proportions: 30 parts of ordinary silicate cement, 3-15 parts of sulphoaluminate cement, 3-15 parts of alkali slag powder, 18-90 parts of composite mineral admixtures, 5-8 parts of surfactants, and 2-5 parts of high molecular polymers; the composite mineral admixtures comprise the following components in the following mass proportions: 20 parts of lithium slag powder, 3-20 parts of magnesium slag powder, and 5-15 parts of blast furnace nickel-iron slag powder.

[0010] Description of some components: The "alkali residue powder" described in the present invention is obtained by crushing the waste residue produced in the process of refining ammonia and brine during the distillation and recovery of ammonia in the production of soda ash by the ammonia-alkali process.

[0011] The "lithium slag powder" described in the present invention is the waste slag produced after lithium is extracted from spodumene ore, which is a powder material with a certain fineness after drying and grinding.

[0012] The "magnesium slag powder" mentioned in the present invention is the waste slag discharged from the smelting of magnesium in a metal magnesium plant, which is a powder material having a certain fineness after being ground.

[0013] The "blast furnace nickel-iron slag powder" described in the present invention is the slag obtained by water quenching and rapid cooling of the molten material discharged during the industrial production of nickel-iron alloy, which is a powder material with a certain fineness after grinding.

[0014] As a further improvement of the present invention, the lithium slag powder satisfies: density ≥ 2.4 g / cm 3 , specific surface area ≥400m 2 / kg, sulfur trioxide mass percentage content ≤8%, 28d activity index ≥95%.

[0015] As a further improvement of the present invention, the magnesium slag powder satisfies: the mass percentage content of magnesium oxide is ≤6%, and the 28d activity index is ≥70%.

[0016] As a further improvement of the present invention, the blast furnace nickel-iron slag powder satisfies: density ≥ 2.8 g / cm 3 , specific surface area ≥400m 2 / kg, 28d activity index ≥80%, the total mass percentage content of SiO2, Al2O3 and CaO ≥70%.

[0017] As a further improvement of the present invention, the alkali slag powder satisfies: the mass percentage of calcium oxide is ≥40%. More preferably, the ordinary Portland cement satisfies: the mass fraction of C3S is ≥50%, the total mass percentage of C3S and C2S is ≥66%, the 3d compressive strength is ≥26.0MPa, and the 28d compressive strength is ≥52.5MPa; the sulphoaluminate cement satisfies: the specific surface area is ≥350 m 2 / kg, initial setting time ≤25min, final setting time ≥180min, 3d compressive strength ≥42.5MPa, 28d compressive strength ≥45MPa.

[0018] It is easy to understand that the surfactant can be selected from commonly used surfactants. For example, the present invention provides a preferred embodiment, wherein the surfactant is selected from one or any of sodium lignin sulfonate, sodium dodecylbenzene sulfonate, and lauramide propylamine oxide; the high molecular polymer includes polyvinyl alcohol (PVA). More preferably, in the sodium lignin sulfonate, the mass percentage of lignin is ≥50%, and the pH (10% aqueous solution) is 4.0-7.0; the active matter content of the sodium dodecylbenzene sulfonate is 70%±2%, the surface tension is ≤35mN / m, and the water content is ≤1%; the surface tension of the above-mentioned lauramide propylamine oxide is ≤35mN / m, the pH (1% solution) is 6.0-8.0, and the foam height is ≤20 mm; the purity of the above-mentioned polyvinyl alcohol is >95%, the molecular weight is 50000-200000, and the solubility is >95%.

[0019] The invention also discloses a special curing agent for premixed fluidized solidified soil of red mudstone, which is prepared by the preparation method of the special curing agent for premixed fluidized solidified soil of red mudstone of the invention.

[0020] The invention also discloses a method for preparing red-bed mudstone premixed fluidized solidified soil, which is characterized in that the special curing agent for the red-bed mudstone premixed fluidized solidified soil of the invention is used in the preparation process.

[0021] The preparation method of the above-mentioned red-bed mudstone premixed fluidized solidified soil can be specifically implemented according to the following steps: S1. Measure the raw materials of the curing agent according to the raw material formula, and the sum of the masses of the raw materials is the amount of the curing agent; S2, premixing the ordinary Portland cement, sulphoaluminate cement, alkali slag powder and composite mineral admixture to obtain a premix; S3, adding the surfactant into a stirring device, adding water and stirring until foaming, and then adding the high molecular polymer and stirring evenly; S4. After the red-bed mudstone is sieved through a 30-50 mm sieve, it is added into the stirring device, stirred evenly, and then the premix is ​​added and stirred evenly again; the amount of the curing agent is 5% to 15% of the mass of the red-bed mudstone.

[0022] The beneficial effects of the present invention are: achieving the reduction of the shrinkage strain of the premixed fluidized solidified soil of red bed mudstone while ensuring that the fluidity and early strength of the premixed fluidized solidified soil meet the construction requirements of the premixed fluidized solidified soil, thereby greatly improving the engineering application performance of the red bed mudstone; solving the problem that when faced with the situation of narrow foundation pit backfill space, complex underground comprehensive pipeline corridor, and multiple narrow and independent backfill sections on the construction surface, in-situ mixing is easily subject to construction restrictions, compaction machinery cannot be used, and manual compaction is likely to cause insufficient density of the backfill soil. DETAILED DESCRIPTION

[0023] The present invention is further described below in conjunction with embodiments.

[0024] For the convenience of comparison, the raw materials used in the following examples and comparative examples are all from the same batch, and the specific parameters of the raw materials are as follows: Lithium slag powder: density 2.74g / cm 3 , specific surface area 469m 2 / kg, sulfur trioxide content by mass percentage is 4.2%, and 28d activity index is 97.6%.

[0025] Magnesium slag powder: magnesium oxide mass percentage content 5.9%, 28d activity index 78.5%.

[0026] Blast furnace nickel-iron slag powder: density 2.93g / cm 3 , specific surface area 427m 2 / kg, 28d activity index is 82.1%, and the total mass percentage content of SiO2, Al2O3 and CaO is 80.4%.

[0027] Ordinary Portland cement: C3S mass fraction 60.3%, the total mass percentage of C3S and C2S 73.9%, 3d compressive strength 28.7MPa, 28d compressive strength 54.5MPa.

[0028] Sulphoaluminate cement: specific surface area 357m 2 / kg, initial setting time 22.1min, final setting time 203min, 3d compressive strength 43.7MPa, 28d compressive strength 47.9MPa.

[0029] Sodium lignin sulfonate: lignin content by mass: 62.8%, pH (10% aqueous solution) is 5.2.

[0030] Sodium dodecylbenzene sulfonate: active matter content 71%, surface tension 33.1mN / m, water content 0.79%.

[0031] Lauramide propylamine oxide: surface tension 30.2mN / m, pH (1% solution) 7.1, foam height 17mm; Polyvinyl alcohol: purity 98.6%, molecular weight 12.4×10 4 , solubility 98%.

[0032] Embodiment 1: Prepare the raw materials by measuring the special curing agent for premixed fluidized solidified soil of red mudstone according to the following formula: 30 parts of ordinary Portland cement, 15 parts of sulphoaluminate cement, 15 parts of alkali slag, 72 parts of composite mineral admixture, 7.5 parts of surfactant (sodium lignin sulfonate), 4 parts of polyvinyl alcohol. The composite mineral admixture is composed of lithium slag powder, magnesium slag powder and blast furnace nickel-iron slag powder in a mass ratio of 20:15:10.

[0033] Embodiment 2: Prepare the raw materials by measuring the special curing agent for premixed fluidized solidified soil of red mudstone according to the following formula: 30 parts of ordinary Portland cement, 10 parts of sulphoaluminate cement, 10 parts of alkali slag, 45 parts of composite mineral admixture, 6 parts of surfactant (sodium dodecylbenzene sulfonate), and 3 parts of polyvinyl alcohol. The composite mineral admixture is composed of lithium slag powder, magnesium slag powder and blast furnace nickel-iron slag powder in a mass ratio of 20:10:10.

[0034] Embodiment three: Prepare the raw materials by measuring the special curing agent for premixed fluidized solidified soil of red mudstone according to the following formula: 30 parts of ordinary Portland cement, 4 parts of sulphoaluminate cement, 5 parts of alkali slag, 26 parts of composite mineral admixture, 6 parts of surfactant (laurylamide propylamine oxide), and 3 parts of polyvinyl alcohol. The composite mineral admixture is composed of lithium slag powder, magnesium slag powder and blast furnace nickel-iron slag powder in a mass ratio of 20:7:11.

[0035] Comparative Example 1 This comparative example is a control experiment of Example 1, except that the alkaline slag and composite mineral admixture are not used. The specific raw material formula is as follows: 30 parts of ordinary Portland cement, 15 parts of sulphoaluminate cement, 7.5 parts of surfactant (sodium lignin sulfonate), and 4 parts of polyvinyl alcohol.

[0036] Comparative Example 2: This comparative example is a control experiment of Example 1, except that the composite mineral admixture is not used. The specific raw material formula is as follows: 30 parts of ordinary Portland cement, 15 parts of sulphoaluminate cement, 15 parts of alkali residue, 7.5 parts of surfactant (sodium lignin sulfonate), and 4 parts of polyvinyl alcohol.

[0037] Comparative Example 3: This comparative example is a control experiment of Example 1, except that no alkali residue is used. The specific raw material formula is as follows: 30 parts of ordinary Portland cement, 15 parts of sulphoaluminate cement, 72 parts of composite mineral admixture, 7.5 parts of surfactant (sodium lignin sulfonate), and 4 parts of polyvinyl alcohol. The composite mineral admixture is composed of lithium slag powder, magnesium slag powder and blast furnace nickel-iron slag powder in a mass ratio of 20:15:10.

[0038] Comparative Example 4: This comparative example is a control experiment of Example 1, except that the composite mineral admixture is all lithium slag powder, and the total amount of the composite mineral admixture used remains unchanged. The specific raw material formula is as follows: 30 parts of ordinary Portland cement, 15 parts of sulphoaluminate cement, 15 parts of alkali slag, 72 parts of lithium slag powder, 7.5 parts of surfactant (sodium lignin sulfonate), and 4 parts of polyvinyl alcohol.

[0039] Comparative Example 5: This comparative example is a control experiment of Example 1, except that the composite mineral admixture is all magnesium slag powder, and the total amount of the composite mineral admixture used remains unchanged. The specific raw material formula is as follows: 30 parts of ordinary Portland cement, 15 parts of sulphoaluminate cement, 15 parts of alkali slag, 72 parts of magnesium slag powder, 7.5 parts of surfactant (sodium lignin sulfonate), and 4 parts of polyvinyl alcohol.

[0040] Comparative Example 6: This comparative example is a control experiment of Example 1, except that the composite mineral admixture is all blast furnace nickel-iron slag powder, and the total amount of the composite mineral admixture used remains unchanged. The specific raw material formula is as follows: 30 parts of ordinary Portland cement, 15 parts of sulphoaluminate cement, 15 parts of alkali slag, 72 parts of blast furnace nickel-iron slag powder, 7.5 parts of surfactant (sodium lignin sulfonate), and 4 parts of polyvinyl alcohol.

[0041] Comparative Example 7: This comparative example is a control experiment of Example 1, except that the composite mineral admixture does not contain lithium slag powder, and the total amount of admixture and the material ratio of magnesium slag powder to blast furnace nickel-iron slag powder remain unchanged. The specific raw material formula is as follows: 30 parts of ordinary Portland cement, 15 parts of sulphoaluminate cement, 15 parts of alkali slag, 72 parts of composite mineral admixture, 7.5 parts of surfactant (sodium lignin sulfonate), 4 parts of polyvinyl alcohol. The composite mineral admixture is composed of magnesium slag powder and blast furnace nickel-iron slag powder in a mass ratio of 15:10.

[0042] Comparative Example 8: This comparative example is a control experiment of Example 1, except that the composite mineral admixture does not contain magnesium slag powder, and the total amount of admixture and the material ratio of lithium slag powder to blast furnace nickel-iron slag powder remain unchanged. The specific raw material formula is as follows: 30 parts of ordinary Portland cement, 15 parts of sulphoaluminate cement, 15 parts of alkali slag, 72 parts of composite mineral admixture, 7.5 parts of surfactant (sodium lignin sulfonate), 4 parts of polyvinyl alcohol. The composite mineral admixture is composed of lithium slag powder and blast furnace nickel-iron slag powder in a mass ratio of 20:10.

[0043] Comparative Example 9: This comparative example is a control experiment of Example 1, except that the composite mineral admixture does not contain blast furnace nickel-iron slag powder, and the total amount of admixture and the material ratio of lithium slag powder to magnesium slag powder remain unchanged. The specific raw material formula is as follows: 30 parts of ordinary Portland cement, 15 parts of sulphoaluminate cement, 15 parts of alkali slag, 72 parts of composite mineral admixture, 7.5 parts of surfactant (sodium lignin sulfonate), 4 parts of polyvinyl alcohol. The composite mineral admixture is composed of lithium slag powder and magnesium slag powder in a mass ratio of 20:15.

[0044] Comparative experiment on the performance of red mudstone premixed fluidized soil: Experimental methods: The curing agent formulas of the above-mentioned embodiments and comparative examples were used to prepare the red mudstone premixed fluidized solidified soil according to the same steps and conditions. The specific steps are as follows: (1) Measure the raw materials of the curing agent according to the raw material formulas of the above embodiments and comparative examples; (2) premixing ordinary Portland cement, sulphoaluminate cement, alkali slag powder (not added in Comparative Examples 1 and 3) and composite mineral admixture (not added in Comparative Examples 1 and 2) to obtain a premix; (3) Add the surfactant to a stirring device, add water and stir until foaming, then add polyvinyl alcohol and stir evenly; (4) After the red mudstone is sieved through a 40 mm sieve, it is added into a stirring device. The amount of the red mudstone added is adjusted so that the amount of the curing agent is 10% of the mass of the red mudstone. After stirring evenly, the above-mentioned premix is ​​added and an appropriate amount of water is added and stirred evenly again to obtain a red mudstone premixed fluidized solidified soil with a solidified soil mass concentration of 65%.

[0045] According to the above method, using the curing agent formulas of Example 1, Example 2, Example 3, Comparative Example 1, Comparative Example 2, Comparative Example 3, Comparative Example 4, Comparative Example 5, Comparative Example 6, Comparative Example 7, Comparative Example 8, and Comparative Example 9, cured soil 1, cured soil 2, cured soil 3, cured soil D1, cured soil D2, cured soil D3, cured soil D4, cured soil D5, cured soil D6, cured soil D7, cured soil D8, and cured soil D9 were prepared respectively.

[0046] In addition, the red mudstone premixed fluidized solidified soil without adding a solidifying agent was prepared according to the above method as solidified soil D0. The specific preparation method is as follows: the red mudstone is passed through a 40 mm sieve and added into a stirring device, and an appropriate amount of water is added and stirred evenly to obtain the red mudstone premixed fluidized solidified soil D0 with a solidified soil mass concentration of 65%.

[0047] Detection method: The prepared red mudstone premixed fluidized soil was tested for compressive strength and expansion according to the "Technical Standard for Engineering Application of Premixed Fluidized Soil" DBJ51_T188-2022. The test results are shown in Table 1.

[0048] The drying shrinkage test was carried out in accordance with the drying shrinkage test in the "Test Procedure for Stabilized Materials of Inorganic Binders for Highway Engineering" JTG E51-2009, and the test results are shown in Table 1.

[0049]

[0050] It can be seen from the performance test results of solidified soil 1, solidified soil 2, solidified soil 3 and solidified soil D0 in Table 1 that the use of the premixed fluidized solidifying agent for red mudstone of the present invention can improve the 28d compressive strength of the premixed fluidized solidified soil for red mudstone by more than 8MPa, and reduce the shrinkage strain by 47×10 -3 The expansion degree reaches more than 324 mm, which greatly improves the engineering application performance of red bed mudstone and can fully meet the construction requirements of premixed fluidized solidified soil.

[0051] From the performance test results of solidified soil 1, solidified soil D1, solidified soil D2 and solidified soil D3 in Table 1, it can be seen that when alkali residue is added to solidified soil D1, the shrinkage strain reduction value is 2.3×10 -3 , while the corresponding reduction value of adding the composite mineral admixture of the present invention alone is 15.2×10 -3 When the two are used in combination, the theoretical reduction value should be less than 17.5×10 -3 , while the actual measured reduction is 24.7×10 -3 The effect is far beyond expectations. It can be seen that the combination of alkali slag and composite mineral admixtures in the present invention has a significant synergistic effect in reducing the shrinkage strain of the red mudstone premixed fluidized solidified soil.

[0052] From the performance test results of solidified soil 1, solidified soil D2, solidified soil D4, solidified soil D5, solidified soil D6, solidified soil D7, solidified soil D8 and solidified soil D9 in Table 1, it can be seen that adding lithium slag, magnesium slag or blast furnace nickel-iron slag and alkaline slag to solidified soil D2 can reduce the shrinkage strain value to a certain extent, and the corresponding reduction values ​​are 5.1×10 -3 , 20.4×10-3 , 18.0×10 -3 If the three are combined into a complex in a ratio of 20:15:10, the theoretical reduction value should be 13.1×10 -3 , while the actual measured reduction is 22.4×10 -3 , which is significantly higher than the theoretical value of 71.0%. It can be seen that the components of the composite mineral admixture in the present invention, lithium slag, magnesium slag and blast furnace nickel-iron slag, when used in combination, have a significant synergistic effect in reducing the shrinkage strain of the red bed mudstone premixed fluidized solidified soil.

Claims

1. A method for preparing a special curing agent for premixed fluidized solidified soil of red mudstone, characterized in that: The production raw material formula includes the following components in the following mass proportions: 30 parts of ordinary Portland cement, 3-15 parts of sulphoaluminate cement, 3-15 parts of alkali slag powder, 18-90 parts of composite mineral admixtures, 5-8 parts of surfactants, and 2-5 parts of high molecular polymers; the composite mineral admixtures include the following components in the following mass proportions: 20 parts of lithium slag powder, 3-20 parts of magnesium slag powder, and 5-15 parts of blast furnace nickel-iron slag powder.

2. The method for preparing the special curing agent for premixed fluidized solidified soil of red mudstone according to claim 1, characterized in that: The lithium slag powder meets the following requirements: density ≥ 2.4 g / cm 3 , specific surface area ≥400m 2 / kg, sulfur trioxide mass percentage content ≤8%, 28d activity index ≥95%.

3. The method for preparing the special curing agent for premixed fluidized solidified soil of red mudstone according to claim 1, characterized in that: The magnesium slag powder meets the following requirements: magnesium oxide mass percentage content ≤ 6%, and 28d activity index ≥ 70%.

4. The method for preparing the special curing agent for premixed fluidized solidified soil of red mudstone according to claim 1, characterized in that: The blast furnace nickel-iron slag powder meets the following requirements: density ≥ 2.8 g / cm 3 , specific surface area ≥400m 2 / kg, 28d activity index ≥80%, the total mass percentage content of SiO2, Al2O3 and CaO ≥70%.

5. The method for preparing a special curing agent for premixed fluidized solidified soil of red mudstone according to any one of claims 1 to 4, characterized in that: The alkali slag powder meets the requirement that the mass percentage of calcium oxide is ≥40%.

6. The method for preparing the special curing agent for premixed fluidized solidified soil of red mudstone according to claim 5, characterized in that: The ordinary Portland cement meets the following requirements: C3S mass fraction ≥ 50%, the total mass percentage of C3S and C2S ≥ 66%, 3d compressive strength ≥ 26.0MPa, 28d compressive strength ≥ 52.5MPa; the sulphoaluminate cement meets the following requirements: specific surface area ≥ 350 m 2 / kg, initial setting time ≤25min, final setting time ≥180min, 3d compressive strength ≥42.5MPa, 28d compressive strength ≥45MPa.

7. The method for preparing a special curing agent for premixed fluidized solidified soil of red mudstone according to any one of claims 1 to 4, characterized in that: The surfactant is selected from one or any combination of sodium lignin sulfonate, sodium dodecylbenzene sulfonate, and lauryl amide propylamine oxide; and the high molecular polymer includes polyvinyl alcohol.

8. A special curing agent for premixed fluidized solidified soil for red bed mudstone prepared by the preparation method of the special curing agent for premixed fluidized solidified soil for red bed mudstone as described in any one of claims 1 to 7.

9. A method for preparing a premixed fluidized solidified soil of red mudstone, characterized in that: The method comprises the step of using the special curing agent for premixed fluidized solidified soil of red mudstone as claimed in claim 8 during the preparation process.

10. The method for preparing the red mudstone premixed fluidized solidified soil according to claim 9, characterized in that: The steps include: S1. Measure the raw materials of the curing agent according to the raw material formula, and the sum of the masses of the raw materials is the amount of the curing agent; S2, premixing the ordinary Portland cement, sulphoaluminate cement, alkali slag powder and composite mineral admixture to obtain a premix; S3, adding the surfactant into a stirring device, adding water and stirring until foaming, and then adding the high molecular polymer and stirring evenly; S4. After the red-bed mudstone is sieved through a 30-50 mm sieve, it is added into the stirring device, stirred evenly, and then the premix is ​​added and stirred evenly again; the amount of the curing agent is 5% to 15% of the mass of the red-bed mudstone.

Citation Information

Cited By

  • High-performance ecological reinforcing agent for roadbed in-situ soil, preparation method and construction method

    CN121537187A